Bilateral Periventricular Nodular Heterotopia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Two unrelated boys, ages 8 and 5 years, with a syndrome of bilateral periventricular nodular heterotopia (BPNH), regional cortical dysplasia, mild mental retardation, and frontonasal malformation (FNM) are reported from the Instituto di Neuropsychiatria Infantile, University of Pisa, Italy, and the Institute of Human Genetics, University of Minnesota Medical School, Minneapolis, MN.